A New Civil Rights Campaign? Policies and Practices to Support Students' Gender Diversity. (September 2018) - Barnard, Janalee; Goodrich, Kristopher M.; Borden, Allison M.
Ms. Barnard is faced with a complex dilemma. The district administrator in charge of lesbian, gay, bisexual, and transgender (LGBT) initiatives and support was presented with a case of a transgender student who wished to attend an overnight field trip and share a room with other students based on her gender identity. Although the district had made previous headway in formatting district policies to fit the needs of transgender students, no procedural directive was available to respond to this new situation. In addition, the superintendent of the district was unsupportive of transgender students. The case was developed for an educational leadership course so that students can discuss the legal issues, role and value conflicts, and theoretical perspective informing policy and practice.